230k views
1 vote
Can someone please help me?

Use mathematical induction to prove the following.

Please show your work.

13.
(1)/(1(2)) +(1)/(2(3))+(1)/(3(4)) +...+(1)/(n(n+1)) =(n)/(n+1)


Any help is greatly appreciated!

User Zztop
by
4.8k points

2 Answers

1 vote

Answer:

im doing the same work but i am working on it ill help you afterwards when i am done .

Explanation:

User Amit Desale
by
5.3k points
4 votes

First show it's true for
n=1. On the left,


\frac1{1\cdot2}=\frac12

On the right,


\frac1{1+1}=\frac12

so the base case
n=1 is true.

Now assume equality holds for
n=k, that


\frac1{1\cdot2}+\frac1{2\cdot3}+\cdots\frac1{k(k+1)}=\frac k{k+1}

We use this assumption to show it also holds for
n=k+1. By hypothesis,


\frac1{1\cdot2}+\frac1{2\cdot3}+\cdots+\frac1{k(k+1)}+\frac1{(k+1)(k+2)}=\frac k{k+1}+\frac1{(k+1)(k+2)}

(the first
k terms condense to
\frac1{k(k+1)})

Combining the fractions gives


(k(k+2))/((k+1)(k+2))+\frac1{(k+1)(k+2)}=(k^2+2k+1)/((k+1)(k+2))=((k+1)^2)/((k+1)(k+2))=(k+1)/(k+2)

which is what we had to establish, thus proving (by induction) equality for all
n.

User Lizmary
by
5.7k points